Use of stochastic patch occupancy models in the California red-legged frog for Bayesian inference regarding past events and future persistence - Alcala, Nicolas (Conservation biology : the journal of the Society for Conservation Biology, 2019)
© 2018 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.